Validation of publication pressure questionnaire‐revised into Chinese nurses from a university hospital - Xinxue Xi; Jing Mao; Tieying Zeng; Dandan Ju (Wiley, 2023)
Abstract Aims To translate and validate the Publication Pressure Questionnaire‐revised (PPQ‐r) among the Chinese nurses. Design A cross‐sectional descriptive study. Methods The classical forward/backward translation of the PPQ‐r was conducted first, and then the psychometric values were tested using the data collected in September, 2021 among 924 Chinese nurses from a university hospital in China by calculating its content validity index, construct validity, both convergent and discriminant validity, and internal consistency reliability following the COSMIN guidelines. Results The proposed three‐factor structure of original PPQ‐r cannot be confirmed in present study. With exploratory factor analysis, a new two‐factor structure with 9 items was extracted, accounting for 62.718% of the variance. Confirmatory factor analysis indicated satisfactory goodness of all fit index values: χ2 = 75.53; df = 23; χ2/df = 3.28; CFI = 0.973; TLI = 0.958; RMSEA = 0.07 and SRMR = 0.047. Both sub‐scales yielded good internal consistency with Cronbach's alpha being 0.845 and 0.876, respectively. The Chinese version of PPQ‐r could be accepted as a reliable and valid tool to measure the Chinese nurses' publication pressure. Patient or Public Contribution Participation of nurses in this study was limited to the data provided through participant survey.